CLASSROOM EXPERIENCE OF THE INTEGRATION OF MATHEMATICS AND MATHEMATICS TEACHING METHODOLOGY COURSES IN THE TRAINING OF FUTURE IN-SERVICE TEACHERS - M.I. Toshpulatova; Aminova Shoira Yuldashevna (European Journal of Humanities and Educational Advancements, 2024)
This study delves into the extended classroom experience of future in-service teachers, specifically focusing on their integration of mathematics and mathematics teaching methodology courses. The research aims to comprehensively understand how this integration influences their preparation for effectively teaching mathematics in a classroom setting. By exploring the extended classroom experience, the study seeks to provide a deeper insight into the practical implications of integrating theoretical knowledge with realworld teaching practices.